Effect of calcium alginate coating on shelf life of frozen lamb muscle - Koushki, Mohammadreza; Azizi, Mohammad Hossein; Koohy-Kamaly, Paliz; Amiri, Zohreh; Azizkhani, Mohammad (Archives of Advances in Biosciences, 2015)
Considering the potential benefits of edible coatings and films for storage of food materials, effect of edible calcium alginate film on shelf life of frozen lamb muscles was studied in the present research. Microbial analyses including total microorganisms count and psychrophilic bacteria count and chemical analyses such as total volatile nitrogen (TVN) and moisture content determination were performed. Coated and uncoated samples had not statistically significant difference in total microbial count, total volatile nitrogen level and moisture content. However, there was statistically significant difference between the coated and uncoated samples in terms of psychrophilic bacteria count (p<0.05). Considering the role of psychrophilic bacteria in meat spoilage, results of the current research confirmed that calcium alginate films may be to some extent effective in shelf life extension of frozen lamb muscle.